A Narrative Inquiry into an ESL Teacher’s Professional Development: Problems and Recommendations - Wei, Liping; Chen, Youna (International Journal of English Language Education, 2022)
Using narrative inquiry, this study investigates an ESL teacher’s experience of professional development, her perspectives of its effectiveness, the challenges encountered, and the changes in teacher knowledge and teaching practices. The focus is on how the teacher participant perceives the problems in professional development and how professional development can best address teachers’ needs in educating ELLs. The problems found to impede teachers from gaining the most from professional development include: (a) failure to tailor to the specific needs of ESL students; (b) neglect of the psychological and emotional well-being of ESL students; (c) lack of empathy for ESL students, (d) lack of content-specific ELL teacher professional development; and (e) professional development not well-attended. Accordingly, recommendations are put forward to render ESL teacher professional development more effective. It is anticipated that this study will provide important insights into how to construct positive professional development that benefits teachers and ESL students to the largest possible degree.